2020
DOI: 10.1186/s12890-020-01217-4
|View full text |Cite
|
Sign up to set email alerts
|

A case of torsades de pointes induced by the third-generation EGFR-TKI, osimertinib combined with moxifloxacin

Abstract: Background: Torsade de pointes (TdP) is a malignant arrhythmia that can be induced by QT internal prolongation due to a variety of factors. Here we report an elderly patient with advanced non-small cell lung cancer (NSCLC) had sudden TdP during hospitalization, which was caused by multiple factors such as osimertinib, moxifloxacin and patient self-factors. Case presentation: An 85-year-old man with advanced NSCLC with brain andbone metastasis was initially treated with gefitinib targeted therapy. After 4 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Although it is useful to reduce disagreement between speakers and to categorize the probability of ADRs, after all, these algorithms neither confirm causality nor do they accurately measure the likelihood of an ADR 3,6 To our knowledge, only three cases of coincidence cardiac dysfunction and QT prolongation caused by Osimertinib have been reported. [7][8][9] The etiology of Osimertinib-induced cardiotoxicity is unclear. It has been suggested that Osimertinib has a similar effect to that Trastuzumab, a monoclonal antibody against human EGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is useful to reduce disagreement between speakers and to categorize the probability of ADRs, after all, these algorithms neither confirm causality nor do they accurately measure the likelihood of an ADR 3,6 To our knowledge, only three cases of coincidence cardiac dysfunction and QT prolongation caused by Osimertinib have been reported. [7][8][9] The etiology of Osimertinib-induced cardiotoxicity is unclear. It has been suggested that Osimertinib has a similar effect to that Trastuzumab, a monoclonal antibody against human EGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…QT interval is lengthened as a result of ventricular potassium current reduction and late sodium current augmentation ( 4 ). Bian et al ( 5 ) reported a first case of 85-year-old male patient with advanced non-small cell lung cancer associated with TdP induced by oral osimertinib (80 mg once daily) and concomitant intravenous moxifloxacin, a broad-spectrum fluoroquinolone antibiotics known to lengthen the QT interval (QTc of 484 ms). Hypokalemia (2.94 mEq/L), impaired left ventricular ejection fraction (41%) and coadministration of moxifloxacin were concluded to underlie the development of TdP.…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemia (2.94 mEq/L), impaired left ventricular ejection fraction (41%) and coadministration of moxifloxacin were concluded to underlie the development of TdP. They lost this case and hence cautioned cardio-oncologists to identify cancer patients at high risk of QT prolongation leading to the development of TdP ( 5 ). Cancer development and apoptosis is governed by driver mutation of signal transduction process mediated by several growth factor receptor including EGFR which is linked to many potassium channels, i.e., Kv1.3 ( 6 ), Kv10.1 ( 7 ), Kv4.3 ( 8 ), and Kir2.3 ( 9 ) are modulated by EGFR kinase via phosphorylation of tyrosine in their specific residues.…”
Section: Discussionmentioning
confidence: 99%
“…However, from the above discussion, it should be noted that gefitinib is not suitable for taking with alkaline food that elevate gastric pH. In addition, during EGFR-TKIs treatment, concomitant medication should also be considered comprehensively to achieve optimal therapeutic outcome [ 14 ].…”
Section: Discussionmentioning
confidence: 99%